Low haemoglobin density as an anaemic indicator in canine babesiosis - K. Rajamanickam; V. Leela (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Low Hemoglobin Density (LHD) is related to functional iron availability and hemoglobin content. To assess the use of LHD as an anaemic indicator in canine babesiosis, 108 dogs with symptoms of canine babesiosis were selected and screened for disease by polymerase chain reaction. Blood samples were collected for estimating haematological variables, serum iron, TIBC, UIBC and LHD. Based on the haemoglobin, PCV and erythrocyte count the animals were grouped into anaemic and non-anaemic populations. LHD% was higher in the anaemic population (P